The Motivational Intelligence Test-Questionnaire (MOTI): development and validation - HUPALOVSKA, Viktoriia; LEVUS, Nadiia (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2025)
Introduction. The article presents the results of the development of a method for the psychological diagnosis of motivational intelligence (MI) in adults – the MotI test-questionnaire, which was the main objective of our work. In accordance with the theoretical criteria expressed in the works of M. Apter and H. Vechorkovska, a battery of 90 items was formed.Methods. The survey involved 1332 individuals aged 18 to 71 years through the online service Google Forms. To confirm validity, the following instruments were applied: the Acceptance and Action Questionnaire (AAQ-II), the Personal Change Readiness Survey (PCRS), the Comprehensive assessment of Acceptance and Commitment Therapy processes (CompACT), the Self-organization of Activity (SOA) scale – an adaptation by Ye. Mandrykova of the English “Time Structure Questionnaire,” and the “Stylistic Self-Regulation of Human Behavior” technique. Data analysis was conducted using the software Statistica 10.0 and Jamovi 2.6.Results. The content of the scales was determined by exploratory factor analysis, which made it possible to identify 9 factors that subsequently formed 10 scales. The final confirmation of the questionnaire structure was carried out by confirmatory factor analysis. The fit indices of the 10-factor model meet the required standards: RMSEA = 0,047; 90% CI [0,045–0,049]; CFI = 0,90; TLI = 0,90; SRMR = 0,046. The internal consistency of the scales was tested using Cronbach’s alpha. Construct validity was examined, including convergent and divergent validity. The retest reliability of the questionnaire meets the required conditions. The normality of data distribution across the extracted scales was verified using the Kolmogorov-Smirnov, Liliefors, Shapiro-Wilk criterion and indicators of skewness and kurtosis. In some scales, a slight shift of the data distribution toward positive values was observed. The theoretical model demonstrated satisfactory agreement with the empirical data. Spearman’s test-retest correlation coefficients (n=215, p
Keywords: motivation; motivational intelligence; psychodiagnostic method; questionnaire; test; validation